P08.33 Azithromycin pharmacokinetics and implications for extended doses for chlamydia trachomatis and other sexually transmitted infections. (13th September 2015) - Kong, FYS; Simpson, JA; Horner, P; Fairley, CK; Hocking, JS
Abstract : Introduction: Chlamydia treatment failure remains concerning with high repeat positive diagnoses of up to 14% in women and 22% for rectal infections in men. Meta-analysis estimates of rectal chlamydia treatment efficacy suggests azithromycin may be 20% less efficacious than doxycycline, but this is based on observational data only – with no RCTs evaluating rectal chlamydia treatment nor any pharmacokinetic data for azithromycin in rectal mucosa. This systematic review will examine the dose-related pharmacokinetics of azithromycin in blood and tissues with discussions on possible considerations of extended regimens to improve efficacy for anorectal infections should a 1 g dose prove suboptimal from RCTs. Methods: Medline and Embase were searched from 1946 to February 2015. Inclusion criteria were: English language, adults and reported pharmacokinetics after any oral dose of azithromycin. Studies of urogenital and rectal tissue were the primary focus but other tissues (excluding eyes) were included. Dose administered and pharmacokinetic parameters such as peak concentration and area under the concentration-time curve (AUC) were extracted. Results: Studies reported high concentrations of azithromycin in cervical, urological, gynaecological, pulmonary, prostatic and oral tissue/fluid after total doses of 500 mg to >2 g. No studies of rectal tissue were reported, however studies of gastric tissue/fluid (a proxy for rectal tissue) showed high concentrations being rapidly attained and sustained for >7 days. Increasing doses results in greater tissue concentrations, which are sustained longer above chlamydia minimum inhibitory concentration (MIC) but with only modest increases in peak blood levels between high and low doses. Similar tissue concentrations were obtained whether the total dose was given over short versus longer duration, suggesting regimens beyond (e.g. >3 days) do not have absorption advantages. Conclusion: Azithromycin concentrations above the MIC are rapidly attained and sustained following treatment. While no data are available in rectal tissue, studies in gastric tissue/fluid suggest adequate rectal concentrations should be obtained. Azithromycin pharmacokinetics also suggest that total doses >1 g given over a few days can be effective in delivering high concentrations to tissues susceptible to chlamydia infections. Disclosure of interest statement: None.